Interaction of the salience network, ventral attention network, dorsal attention network and default mode network in neonates and early development of the bottom-up attention system - Onofrj, Valeria; Chiarelli, Antonio Maria; Wise, Richard; Colosimo, Cesare; Caulo, Massimo (Brain structure & function, 2022)
The salience network (SN), ventral attention network (VAN), dorsal attention network (DAN) and default mode network (DMN) have shown significant interactions and overlapping functions in bottom-up and top-down mechanisms of attention. In the present study, we tested if the SN, VAN, DAN and DMN connectivity can infer the gestational age (GA) at birth in a study group of 88 healthy neonates, scanned at 40 weeks of post-menstrual age, and with GA at birth ranging from 28 to 40 weeks. We also ascertained whether the connectivity within each of the SN, VAN, DAN and DMN was able to infer the average functional connectivity of the others. The ability to infer GA at birth or another network's connectivity was evaluated using a multivariate data-driven framework. The VAN, DAN and the DMN inferred the GA at birth (p < 0.05). The SN, DMN and VAN were able to infer the average connectivity of the other networks (p < 0.05). Mediation analysis between VAN's and DAN's inference on GA at birth found reciprocal transmittance of change with GA at birth of VAN's and DAN's connectivity (p < 0.05). Our findings suggest that the VAN has a prominent role in bottom-up salience detection in early infancy and that the role of the VAN and the SN may overlap in the bottom-up control of attention.
Keywords: Humans; magnetická rezonanční tomografie; kojenec; Child, Preschool; Nerve Net; Default Mode Network; lidé; nervová síť; gestační stáří; Infant, Newborn; mozek; Infant; Brain; předškolní dítě; Gestational Age; novorozenec; mapování mozku; default mode network; Magnetic Resonance Imaging; Brain Mapping